PERANAN BADAN KEMAKMURAN MASJID ( BKM ) AL-IKHLAS DALAM MENINGKATKAN KERUKUNAN BERAGAMA DI LINGKUNGAN XII KELURAHAN TANJUNG SARI KECAMATAN MEDAN SELAYANG - Zulkarnaen Guchi, Ar-Rahim, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
The Mosque Prosperity Agency is an institution that is sheltered and works in carrying out its vision and mission. However, the Mosque Prosperity Agency plays the role of Implementation and Mobilization to expedite the activities of Muslims in worship activities. Religious harmony is a condition of inter-religious relations which is based on tolerance, mutual understanding, mutual respect, respect for equality in life, practicing religious teachings and cooperation in social and national life. and state. The problem formulation of this research is the role of BKM in increasing religious harmony and the obstacles it faces. This research uses a descriptive qualitative method, namely a research method that can be used to explore and understand the meaning that comes from social or humanitarian problems. Results The Qualitative Research Process involves important efforts such as: asking questions, developing procedures, collecting certain data from informants or participants. The conclusion of this study is that BKM organizes such as PHBI, Public Help Unions (STM), Thursday night announcements, Friday night announcements, announcements for mothers, Mosque Youth and the Environmental Care Forum (Forduling) to increase religious harmony in the environment. Empowering religious organizations, resolving conflicts between religious communities, guiding religious people to increase faith and piety to Allah SWT in an atmosphere of harmony both internally and externally between religious communities.